2021
DOI: 10.1007/s40519-021-01269-3
|View full text |Cite
|
Sign up to set email alerts
|

The negative impact of obesity on the occurrence and prognosis of the 2019 novel coronavirus (COVID-19) disease: a systematic review and meta-analysis

Abstract: Purpose The 2019 novel coronavirus (COVID-19) is an emerging pandemic, with a disease course varying from asymptomatic infection to critical disease resulting to death. Recognition of prognostic factors is essential because of its growing prevalence and high clinical costs. This meta-analysis aimed to evaluate the global prevalence of obesity in COVID-19 patients and to investigate whether obesity is a risk factor for the COVID-19, COVID-19 severity, and its poor clinical outcomes including hospitalization, in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 102 publications
3
22
0
1
Order By: Relevance
“…According to our results and after controlling for potential confounders, clinical variables previously linked to poor prognoses regarding SARS-CoV-2 infection, such as age, BMI and arterial hypertension, were positively associated with increasing levels of anti-S protein antibody titer after vaccination [27][28][29][30][31], but exclusively in infected/Nprot+ subjects. Although previous work reported that smoking harbors protection against SARS-CoV-2 infection, we and others have found lower antibody levels after vaccination associated with this habit [7,31,32].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…According to our results and after controlling for potential confounders, clinical variables previously linked to poor prognoses regarding SARS-CoV-2 infection, such as age, BMI and arterial hypertension, were positively associated with increasing levels of anti-S protein antibody titer after vaccination [27][28][29][30][31], but exclusively in infected/Nprot+ subjects. Although previous work reported that smoking harbors protection against SARS-CoV-2 infection, we and others have found lower antibody levels after vaccination associated with this habit [7,31,32].…”
Section: Discussionsupporting
confidence: 59%
“…However, none of these works evaluated this vaccine's response in subjects previously infected by SARS-CoV-2 who had lost their response against the nucleocapsid protein (N protein) and, with it, a substantial part of the protection conferred by the infection. Other works reported the influence on the vaccine of different factors previously associated with the severity of the infection, namely, sex, age, obesity, arterial hypertension and smoking habit, providing results that show some inconsistencies across these studies [26][27][28][29][30][31][32][33][34][35]. Importantly, the time elapsed from vaccination and/or from infection to serology have a huge impact on the measurement of the antibody titer, but these data were not always controlled in the previous works.…”
Section: Introductionmentioning
confidence: 93%
“…Apart from the effectiveness of lockdown for infection control during the pandemic, young people with obesity should be monitored carefully to prevent health problems due to physical inactivity when implementing lockdown and social distancing. Importantly, obesity is significantly associated with the increased risk of susceptibility to COVID-19 (odds ratio (OR), 2.42; 95% CI, 1.58-3.70), severity of COVID-19 (OR, 1.62; 95% CI, 1.48-1.76), hospitalization (OR, 1.75; 95% CI, 1.47-2.09), and death (OR, 1.23; 95% CI, 1.06-1.41) [21].…”
Section: Physical Activity During the Covid-19 Pandemicmentioning
confidence: 99%
“…BMI has been established as a risk factor for adverse COVID outcomes, including increased risk for hospitalization [63], ICU admission [64], mechanical ventilation [65] and death [66].…”
Section: Discussionmentioning
confidence: 99%